Legal Protection for Victims of Medical Practitioner Misconduct in Indonesia and Malaysia: (Perlindungan Undang-Undang terhadap Mangsa Salah Laku Pengamal Perubatan di Indonesia dan Malaysia) (Kanun: Jurnal Undang-undang Malaysia, 2020)
Nowadays, it is a norm for patients to claim for medical negligence. Negligence includes the offence of giving a wrong diagnosis, mistreatment and failure to do treatment which resulting in patients getting disability or death. The objectives of the article are to discuss the efforts made to prevent the occurrence of medical misconduct, and the law that protects victims of medical misconduct. This article is based on qualitative research and using a comparative socio-legal method. The research uses a variety of data collection methods i.e. library search, documentation review, observation, interviews and questionnaires. Data were analyzed by content analysis and t-test. The result shows there are five parameters that have the sig